Multimedia Environmental Fate and Transport Model of dichlorodiphenyltrichloroethane (DDT): Case Study Sayong River Watershed, Johor, Malaysia - Z.A. Ghani,; A.N. Anuar,; Z.A. Majid,; Yoneda, M. (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study describes the development of a multimedia environmental fate and transport model of dichlorodiphenyltrichloroethane (DDT) at Sungai Sayong watershed. Based on the latest estimated DDT emission, the DDT concentrations in air, soil, water and sediment as well as the transfer processes were simulated under the equilibrium and steady-state assumption. Model predictions suggested that soil and sediment was the dominant sink of DDT. The results showed that the model predicted was generally good agreement with field data. Compared with degradation reaction, advection outflow was more important processes occurred in the model. Sensitivities of the model estimates to input parameters were tested. The result showed that vapour pressure (Ps) and organic carbon water partition coefficient (KOC) were the most influential parameters for the model output. The model output-concentrations of DDT in multimedia environment is very important as it can be used in future for human exposure and risk assessment of organochlorine pesticides (OCPs) at Sungai Sayong Basin.